Total synthesis of the proposed structure of astakolactin - Tonoi, Takayuki; Mameda, Keisuke; Fujishiro, Moe; Yoshinaga, Yutaka; Shiina, Isamu (Beilstein Journal of Organic Chemistry, 2014)
The first total synthesis of the proposed structure of astakolactin, a sesterterpene metabolite isolated from the marine sponge Cacospongia scalaris, has been achieved, mainly featuring Johnson–Claisen rearrangement, asymmetric Mukaiyama aldol reaction and MNBA-mediated lactonization.
Keywords: aldol reaction; astakolactin; lactonization; MNBA; terpenoids